ON A SWARM OF CRESEIS ACICULA RANG (PTEROPODA) IN THE KARWAR WATERS - Naomi, T S (Indian Journal of Fisheries, 2011)
The pteropods represented by Creseisacicula, Diacria sp. and Cavolinia sp. occurredoccasionally in the zooplankton samplescollected from the fishing grounds of theKarwar region. Generally the frequencyof occurrence of C. acicula was greater thanthose of the others during the years 1980-'82. The number of specimens of C. aciculaper sample used to be a few and neverexceeded 7,216 recorded on 10-4-1980 untilan unusually large number 140,636 wasobserved in a surface haul of zooplanktonon 16-10-1982.